Phenotypic and molecular characterization of the resistance to quinone outside inhibitors in Fusarium graminearum - Andrade, Sheila Maria Pereira de (2021)
Fusarium Head Blight (FHB) is a fungal disease of small grains caused mainly by Fusarium graminearum. In Brazil, farmers rely on fungicides to minimize yield losses caused by a complex of foliar and floral diseases, as well as to reduce mycotoxin contamination due to FHB. Usually, a range of active ingredients are used in isolation or dual premixes that include a triazole (DMI) and a quinone outside inhibitor (QoI) fungicides. Comprehensive information on the sensitivity/resistance of F. graminearum to fungicides is available only for DMIs, while for QoI, data are scarce and controversial. A total of 225 strains were studied in this work and they were split into two geographical subcollections: one from Rio Grande do Sul (RS), 125 strains, and other from Paraná (PR), 100 strains. The in vitro sensitivity of F. graminearum isolates was assessed through the conidia germination assay and tested concentrations for azoxystrobin were 0, 0.001, 0.01, 0.1, 1,10 and 100 μg mL-¹, while for pyraclostrobin were 0, 0.05, 0.5, 1.0, 5.0 and 10 μg mL-¹. Effective concentration leading to 50% inhibition (EC 50 ) of conidial germination was obtained based on three-parameter Weibull function. Isolates, in which the EC 50 was not previously determined, were screened by discriminatory doses (DD) for both fungicides. Molecular analysis of the cytb gene was performed and nine isolates were selected and sequenced. The median EC 50 value for azoxystrobin (n = 25) was 2.20 μg mL-¹ in the PR collection and 4.04 μg mL-¹ in the RS collection. For pyraclostrobin (n = 50), the median EC 50 was 0.28 μg mL-¹ in the PR collection and 0.24 μg mL-¹ in the RS collection. These median values are greater than the maximum EC 50 reported in previous works. Shapiro-Wilk test indicated that EC 50 values were normally distributed (P = 0.23), and no significant difference was observed among the collections. A comparison between the two fungicides showed significant differences between them and pyraclostrobin was more fungitoxic than azoxystrobin. There was no significant correlation between the EC 50 values of the two fungicides. Based on the DD, 50% of the strains analysed were classified as less sensitive to azoxystrobin in the PR collection (n = 75) and 28% in the RS collection (n = 100). For pyraclostrobin, 33% of the strains were classified as less sensitive in the PR collection and 18.8% in the RS collection. We also observed an increase in the relative frequency of less sensitivity isolates between five years (2007-2011) in the RS collection. Sequence alignments showed no point mutation in any hot spot (F129L, G137R, G143A) even in the isolates with highly EC 50 . In conclusion, we are able to set a sensitivity profile for F. graminearum populations, however the resistance mechanism associated with QoI fungicides remains unclear. Our study suggested a shift towards less sensitive populations and further studies shall be conducted for monitoring more contemporary isolates from these regions, both in vitro and in vivo experiments, as well as testing other mechanisms of resistance. Keywords. Fusarium Head Blight. Strobilurin. Gibberella zeae. Triticum aestivum